PSMC2 is a Novel Prognostic Biomarker and Predicts Immunotherapeutic Responses: From Pancreatic Cancer to Pan-Cancer - Huang W; Qian Z; Shi Y; Zhang Z; Hou R; Mei J; Xu J; Ding J (Dove Medical Press, 2023)
Wei Huang,1,* Zhengtao Qian,2,* Yuxin Shi,1,3,* Zheming Zhang,3 Rui Hou,1,3 Jie Mei,1,3 Junying Xu,1 Junli Ding1 1Department of Oncology, the Affiliated Wuxi People's Hospital of Nanjing Medical University, Wuxi, 214023, People's Republic of China; 2Department of Clinical Laboratory, Changshu Medicine Examination Institute, Changshu, 215500, People's Republic of China; 3Wuxi School of Clinical Medicine, Nanjing Medical University, Wuxi, 214023, People's Republic of China*These authors contributed equally to this workCorrespondence: Junli Ding; Junying Xu, Email dingjunliletters@163.com; doctorxjy123@163.com; xujunying@wuxiph.comBackground: Proteasome 26S subunit ATPase 2 (PSMC2) is a part of the 19S regulatory complex, which catalyzes the unfolding and transport of substrates into the 20S proteasome. Our previous research demonstrated that PSMC2 participates in the tumorigenesis and progression of pancreatic cancer (PC). However, no systematic analysis has been conducted to conclude its expression pattern and correlation with tumor immunity.Aim: To investigate the expression level of PSMC2 in PC, its prognostic value and its relationship with tumor immunity.Methods: In numerous public and internal cohorts, the expression, prognostic significance, and immunological connections of PSMC2 in PC were investigated. Additionally, using data from The Cancer Genome Atlas (TCGA), a pan-cancer analysis was carried out to examine PSMC2's immunological assocaition, and the predictive power of PSMC2 for immunotherapy was also evaluated in numerous public cohorts.Results: PSMC2 was overexpressed in tumor tissues and linked to unfavorable prognosis in PC. PSMC2 was not only positively correlated with TIICs, also positively correlated with immune checkpoints in PC. In addition to PC, PSMC2 was expected to be an indicator of high immunogenicity in most cancer types. Importantly, PSMC2 could predict the immunotherapeutic responses in various cancer types, including urothelial carcinoma and breast cancer.Conclusion: From PC to pan-cancer analysis, we report that PSMC2 is a novel prognostic biomarker in multiple cancer types. PSMC2 is related to the immuno-hot phenotype and predicts the outcome of immunotherapy. Therefore, the current study emphasizes that cancer patients with high PMSC2 expression should actively receive immunotherapy to improve their prognosis.Keywords: PSMC2, tumor immunity, pancreatic cancer, biomarker, bioinformatics